Rekrutmen Pegawai Menuju Kinerja Organisasi yang Berkualitas dalam Perspektif MSDM dan Islam - Iskarim, Mochamad (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2017)
Success in employee recruitment system is a starting point toward a well performing organization. To gain employees who are match with the task requirements of an organization, requires some procedures, such as: job identification, job analysis, recruitment sources, recruitment method, and candidate interview and selection, as well as job offer. Referring to Islamic conception on employee recruitment, this research found numbers of principles in recruitment, they are: (a). merit system, that means reward system is given based on quality of services performed, (b). Belief in God and having high moral commitment to reach organizational objective, (c). avoid nepotism practices or like and dislike, and all kinds of bribery in the administration and management.   Keywords: Organizational performance, recruitment, human resources, merit system